INTEGRATED AREA MASTERPLAN PLANNING OF THE GOVERNOR'S OFFICE OF WEST SUMATRA - Aidil Surya Ade Putra; Irnawati Siregar (Ikatan Dosen Menulis, 2025)
The masterplan planning aims to improve the container of provincial government activities in carrying out services to the community and public interests and can act as a philosophical, functional, technical, monumental symbol, and has an openness function that reflects the city or Province of West Sumatra. The condition of the governor's office as a control of government coordination, policy and development management ranks, public services and the economic sector, security and emergency response, equipment and services, historical heritage and education, is not optimal because the location of the building is scattered in several places. The method used in data collection is a qualitative method guided by the data components needed in the masterplan planning of the integrated area of ​​the governor's office of West Sumatra. The recommendation of the masterplan planning results of the West Sumatra governor's office is the formation of interconnected buildings, in the new building a 2-story basement was made as a solution for parking capacity, the 1st floor and then offices connected by connecting bridges, the top floor as an open area, disaster mitigation. This condition shows an integrative scheme between administrative functions and supporting activities that support employee productivity and welfare within one building complex.